Memory - Birnbaum, Daniel; Bourriaud, Nicolas; Farr, Ian, 1960-; Whitechapel Gallery Ventures (London : Whitechapel Gallery ; Cambridge, Mass. : The MIT Press, 2012)
Marina Abramovic; Eija-Liisa Ahtila; Kutlug Ataman; Uta Barth; Tom Burr; Sophie Calle; Paul Chan; Desire Machine Collective; Stan Douglas; Cherryl Dunye; Kota Ezawa; Jef Geys; Liam Gillick; Shumona Goel; Felix Gonzalez-Torres; Sharon Hayes; Susan Hiller; Roni Horn; Craigy Horsfeld; Pierre Huyghe; Amar Kanwar; William Kentridge; Idreis Kahn; Zoe leonard; Ilan Lieberman; Glen Ligon; Elisabeth Manchester; Kabir Mohanty; Robert Morris; RabihMroué; Jun Nguyen-Hatsushiba; Uriel Orlow; Philippe Parreno; Walid Raad; Anri Sala; Fazal Sheikh; Lorna Simson; Vivan Sundaram. Luc Tuymans
Co-published by Whitechapel Gallery and the MIT Press.
Formerly CIP.
boek